Testing the conservation of Quercus spp. microsatellites in the cork oak, Q-suber L. - Hornero, J; Gallego, F J; Martinez, I; TORIBIO, M (SILVAE GENETICA, 2001)
The transferability of microsatellite (SSR) loci from Quercus spp. to cork oak (Quercus suber L.) was investigated. Semi-automated analysis of fluorescently-labelled PCR fragments was used to test 24 primer sets developed for Q. myrsinifolia BLUME, Q. petraea (MAT7.) LIEB. and Q. robur L. in 41 cork oak trees from four stands covering the main area of distribution of the species in Spain. Successful cross-species events occurred for 13 loci (54%). Two of them were monomorphic and another two appeared as multilocus. High levels of genetic variability were detected both for the number of alleles, 62 (7.5 per polymorphic locus, with a maximum number of 19 in locus ssrQpZAG110) and for the expected heterozygosity (mean H-E = 0.648). These results were much higher than those previously reported by other authors using allozyme loci. The usefulness of the. SSR loci successfully amplified for studies on population genetics of cork oak is discussed.
Keywords: Cork oak; Fagaceae; microsatellites; Quercus suber